Patterns of Pre-pregnancy Care Usage among Reproductive Age Women in Kedah, Malaysia - Rozaimah ABU TALIB; Idayu Badilla IDRIS; Rosnah SUTAN; Norizan AHMAD; Norehan ABU BAKAR (Tehran University of Medical Sciences, 2018)
Background: This cross-sectional was aimed to assess the prevalence of pre-pregnancy care services usage and its determinant factors among women of reproductive age in Kedah, Malaysia. Methods: Overall, 1347 respondents who attended 24 government health clinics, were chosen using systematic multistage random sampling. A validated self-administered questionnaire which consisted of sections including socio-demographic characteristics, social support, knowledge on pre-pregnancy care, perception on risk of pregnancy, health status, as well as intention and awareness on pre-pregnancy care services were distributed. Results: The prevalence of utilization of pre-pregnancy care services was still low i.e. 44.0%. Bivariate and multivariate analysis showed consistent significant level between all factors and pre-pregnancy care usage except for family planning practice. The factors that showed significant difference with the usage of pre-pregnancy care services were age of more than 35 (P<0.001), high education level (P<0.001), non-working mothers (P<0.001), multipara (P=0.001), awareness on the existence of pre-pregnancy care services in government health facilities (P<0.001), intention to use the services (P=0.0030), having medical illness (P=0.005), having social support (P=0.001), high knowledge (P<0.001), and positive perception (P<0.001). Conclusion: Low usage of pre-pregnancy care services can be improved through health screening on reproductive-aged women with positive determinant factors at the triage level in integrated clinics. Information and knowledge on pre-pregnancy services should be disseminated among community members through various means including roadshows and pre-wedding workshops.